2020
DOI: 10.1186/s13071-020-3993-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Leishmania infection and exposure to Phlebotomus perniciosus using minimal and non-invasive canine samples

Abstract: Background: In endemic areas of zoonotic leishmaniosis caused by L. infantum, early detection of Leishmania infection in dogs is essential to control the dissemination of the parasite to humans. The aim of this study was to evaluate the serological and/or molecular diagnostic performance of minimally and non-invasive samples (conjunctiva cells (CS) and peripheral blood (PB)) for monitoring Leishmania infection/exposure to Phlebotomus perniciosus salivary antigens in dogs at the beginning and the end of sand fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…The estimated posterior median of Leishmania seroprevalence of 13.4% obtained with both models in the dogs from Portugal was similar to the percentage obtained with the total number of canine sera tested with L. infantum IgG-ELISA ® , i.e. 12.5% and 13.9% at the beginning and end of the sand fly season, respectively [ 23 ]. The three techniques used in this study were found to be specific for the detection of antibodies against Leishmania in the Portuguese population of dogs, with specificity values between 92.5 and 99.1%.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The estimated posterior median of Leishmania seroprevalence of 13.4% obtained with both models in the dogs from Portugal was similar to the percentage obtained with the total number of canine sera tested with L. infantum IgG-ELISA ® , i.e. 12.5% and 13.9% at the beginning and end of the sand fly season, respectively [ 23 ]. The three techniques used in this study were found to be specific for the detection of antibodies against Leishmania in the Portuguese population of dogs, with specificity values between 92.5 and 99.1%.…”
Section: Discussionmentioning
confidence: 53%
“…Serum samples from a total of 378 dogs (194 from Portugal and 184 from Brazil) obtained in previous epidemiological studies [ 16 , 23 ] were analyzed. Portuguese dogs were from four private kennels of the Metropolitan Lisbon region, and domiciled Brazilian dogs were from the municipality of Camaçari, located in the State of Bahia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are somewhat surprising as yellow-related, and antigen 5-related proteins are known as suitable exposure markers in other sand fly species. Yellow-related proteins were demonstrated as valid markers of human exposure to Lutzomyia longipalpis ( Souza et al, 2010 ) and Phlebotomus orientalis ( Sumova et al, 2018 ) and repeatedly of canine exposure to Phlebotomus perniciosus ( Martín-Martín et al, 2014 , Kostalova et al, 2015 , Kostalova et al, 2017 , Risueño et al, 2018 , Willen et al, 2019 , Maia et al, 2020 ). Antigen 5-related proteins were proposed as human exposure markers to Lutzomyia intermedia ( Carvalho et al, 2017 ) and P. orientalis ( Sumova et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of sand fly salivary proteins has already been revealed for several sand fly species (Coutinho-Abreu and Valenzuela, 2018 ; Oliveira et al, 2020 ; Polanska et al, 2020 ), including P. perniciosus (Anderson et al, 2006 ; Martin-Martin et al, 2013 ). Several salivary proteins from this sand fly species have been expressed and further tested primarily as markers of exposure (Lestinova et al, 2017 ; Velez et al, 2018 ; Willen et al, 2018 , 2019 ; Risueno et al, 2019 ; Burnham et al, 2020 ; Maia et al, 2020 ). However, the functional studies of P. perniciosus salivary recombinant proteins are very limited (Sumova et al, 2019 ), and so far there is no study on their immunomodulatory properties.…”
Section: Introductionmentioning
confidence: 99%